UTAUT UNTUK MEMAHAMI TINGKAT PENERIMAAN PENGGUNA SISTEM INFORMSI PT.SWADHARMA SARANA INFORMATIKA CILACAP - Fiby Nur Afiana; Eka Tripustikasari; Reta Dwi Anggraeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
PT.Swadharma Sarana Informatika is a company that provides Information Technology facilities and the management of Automated Teller Machines (ATMs), using an Application Operational System (SOA) to support website-based or online financial reports for 24 hours. In the implementation of input there are complaints by users or users of the SOA application. The user factor is a very important factor to consider in implementing a new system, empirical studies are needed to evaluate the real conditions of the user for the new application being applied. UTAUT (Unified Theory Of Acceptance And Use Of Technology). This method is considered suitable for understanding the level of user acceptance with the variables used are (performance expectancy), effort expectancy, social influence, faciliating conditions, gender and user behavior. Use Behavior) on the SOA acceptance rate. Validity Test, Reliability Test, Normality Test using the One Sample Kolmogonov-Smirnov method, Linearity Test, Heteroscedasticity Test and Simple Linear Regression Test were used to determine the results of this study, the results obtained state that there is a significant positive influence on the Performance Expectancy variable. ), Business Expectancy Variable (Effort Expectancy), Social Influence Variable and Faciliating Condition Variable have a positive effect on the Actor's Intention (Behavioral Intention).